The Effect of Work-Life Balance and Workload on Job Satisfaction at the Perumda Tirta Musi Office - Muhammad Adhitia Abdurrahman; Zunaidah Zunaidah; Yuliani Yuliani (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study aims to determine whether work life balance and workload affect job satisfaction at the Perumda Tirta Musi office. Perumda Tirta Musi Palembang is a Regionally-Owned Enterprise managed by the Palembang City Government. This study uses primary data by distributing questionnaires to employees. The population used is 105 respondents where the entire population is used as a sample. The analysis technique used is multiple linear regression analysis processed using IBM SPSS version 26. The results obtained are Work Life Balance has a positive and significant effect on Job Satisfaction and Workload has a positive and significant effect on Job Satisfaction.